FACTORS CAUSING PARTAI DEMOKRAT INDONESIA VICTORY IN THE 2019 LEGISLATIVE ELECTION IN LAMPUNG PROVINCE - Widia Novita Lukitasari WA (Kemudi, 2022)
The Indonesian Democratic Party of Struggle in Lampung Province is one of several parties that participated in the 2019 legislative elections and through the rule of law, the PDI-P has the most seats in the Lampung Provincial DPRD, then has the right to propose its cadres to sit as Chair of the Lampung Provincial DPRD.. The focus of writing the paper is the factor that caused the PDI-P's victory in the 2019 Legislative Election in Lampung Province.Peinfluence figures have a dominant role in the electoral system that uses the majority vote system. Competence and credibility of candidates for imaging and electability of the candidates concerned. The key to the PDI-P's victory in the 2019 election in Lampung Province is having militancy capital or traditional voters who are loyal to the party's choice. The nationally valid traditional electorate is the first determining factor. Next is the high level of penetration of legislative candidates in influencing voters.